سخن سردبیر - عباسی, محمود (مجله اخلاق پزشکی - علمی پژوهشی, 2016)
Medical ethics is actually a four- way science. Since the 1970s, many different branches of science like philosophy, history, law, medicine and psychology have paid a great deal of attention to it. Developments in medical technology and science, along with plenty of other human technical advances have led to new approaches in moral Issues. Nowadays, in respect of the relation ship between physicians and patients, some new notions such as human autonomy, value and quality of life, the right to life and safety besides human dignity have had a considerable influence. Hence, many medical ethics jurists belong to different subject areas....